2008
DOI: 10.1128/jvi.00704-08
|View full text |Cite
|
Sign up to set email alerts
|

S Acylation of the Hemagglutinin of Influenza Viruses: Mass Spectrometry Reveals Site-Specific Attachment of Stearic Acid to a Transmembrane Cysteine

Abstract: S acylation of cysteines located in the transmembrane and/or cytoplasmic region of influenza virus hemagglutinins (HA) contributes to the membrane fusion and assembly of virions. Our results from using mass spectrometry (MS) show that influenza B virus HA possessing two cytoplasmic cysteines contains palmitate, whereas HA-esterase-fusion glycoprotein of influenza C virus having one transmembrane cysteine is stearoylated. HAs of influenza A virus having one transmembrane and two cytoplasmic cysteines contain bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
78
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 20 publications
(29 reference statements)
2
78
0
Order By: Relevance
“…Two cysteines present within the cytoplasmic tail (CT) sequence and one cysteine in the transmembrane domain (TM) sequence of HA are S acylated by two palmitates (CT cysteines) and one stearic or palmitic acid (TM cysteine), respectively (34,35). The role of HA acylation has been studied extensively since these cysteines are conserved at their respective positions to a greater extent than other residues among all otherwise highly variable HA subtypes.…”
mentioning
confidence: 99%
“…Two cysteines present within the cytoplasmic tail (CT) sequence and one cysteine in the transmembrane domain (TM) sequence of HA are S acylated by two palmitates (CT cysteines) and one stearic or palmitic acid (TM cysteine), respectively (34,35). The role of HA acylation has been studied extensively since these cysteines are conserved at their respective positions to a greater extent than other residues among all otherwise highly variable HA subtypes.…”
mentioning
confidence: 99%
“…3B). To prove the specificity of HA-M2 clustering, we used an HA mutant in which the raft- targeting features-S acylation at three cysteine residues (12) and the sequence VIL in the exoplasmic half of the transmembrane domain (19,26)-had been replaced by serines and alanines, respectively (6). A similar mutant of HA has been shown by electron microscopy to be uniformly distributed on the plasma membrane, in contrast to the patched appearance of wild-type HA (26).…”
mentioning
confidence: 99%
“…Although the function of heterogenous S-acylation of proteins with different fatty acids was not known, it was shown that the length and composition of the transmembrane seuqences as well as the cytoplasmic sequences can influence the choice of fatty acids for acylation [64][65][66]. Identification and quantification of acyl moieties are essential for understanding the detailed mechanisms of protein palmitoylation.…”
Section: Identification and Quantification Of Acyl Moietiesmentioning
confidence: 99%